Playlab the Philippine center for digital game design and development - Castaneda, Bernice C.
Gaming tourism in the Philippines has expanded significantly thus leading to game developers and even enthusiasts to form organizations to endorse Filipino talent in game design and development. In line with the campaign to promote the full potential of Philippine digital gaming and animation, the study would like to prove that creating transparent, flexible, and highly interactive spaces can maximize the full potential of creativity, productivity, and communal culture. The results will be translated into a Philippine Center for Digital Gaming with more transformable and artistic-induced spaces that can cater to all game designers, programmers, and fanatics. Work and play.